A numerical solution of the vibration equation using modified decomposition method - Das S. (My University, 2025)
In the present paper the well-known vibration equation for very large membrane with the help of powerful modification of Adomian decomposition method proposed by Wazwaz [A reliable modification of Adomian decomposition method, Applied Mathematics and Computation 102 (1999) 77-86] has been solved. By using initial value, the explicit solutions of the equation for different cases have been derived, which accelerate the rapid convergence of the series solution. The present method performs extremely well in terms of efficiency and simplicity. Numerical results for different particular cases of the problem are presented graphically. © 2008 Elsevier Ltd. All rights reserved.